Ultrahigh Emulsion Separation Flux and Antifouling Performance of MIL‐100(Fe)@Graphene Oxide Membrane Enabled by its Superhydrophilicity and Self‐Cleaning Ability. (23rd March 2022) - Wang, Rui; Zhong, Yunqian; He, Ruijie; Zou, Yanzhao; Yang, Juncai; Fu, Miao; Zhang, Ruiyang; Zhou, Ying
Abstract: The development of microfiltration (MF) membranes with a high separation flux and antifouling ability is an ultimate goal for the purification of emulsified oily wastewater by MF techniques. Herein, a dual‐functional MIL‐100(Fe)@graphene oxide (MIL‐100(Fe)@GO) membrane is fabricated by in situ growth of MIL‐100(Fe) with a graphene oxide (GO) nanosheet. The porous MIL‐100(Fe)@GO composite endows the MF membrane with superhydrophilicity and demulsification functions. The MIL‐100(Fe)@GO membrane achieves an outstanding water permeation flux of 12 457 L m −2 h −1 bar −1, as encouraged by the versatility of MIL‐100(Fe) in enabling superhydrophilicity of the MIL‐100(Fe)@GO membrane and providing rich water permeation channels. An impressive emulsion separation efficiency of >99% and maximum emulsion separation flux of 5529 L m −2 h −1 bar −1 are thus delivered by the MIL‐100(Fe)@GO membrane. Moreover, a 131% recovery ratio of emulsion separation flux (7135 L m −2 h −1 bar −1 ) is attained with this system after regeneration by ethanol. In virtue of the demulsification of MIL‐100(Fe), the rational design of the MIL‐100(Fe) hybrid membrane exhibits a self‐cleaning effect on the emulsion separation. The demonstrated high performance of the membrane system opens up new avenues for the development of membranes with antifouling abilities and ultrahigh flux for emulsion separation. Abstract : In situ growth of MIL‐100(Fe)@GO shrinks a graphene oxide nanosheet to form a superhydrophilic interconnected network, enabling fabrication of a microfiltration (MF) membrane that realizes an incredible emulsion separation flux. Due to the coupling of demulsification and microfiltration, this membrane exhibits an antifouling ability during the emulsion separation.